Elevated expression of Toll-like receptor 4 and cytokines in both serum and myometrium at term may serve as promising biomarkers for uterine activation preceding labor - Chen, Zixi; Li, Jinpeng; Xu, Wenjuan; Wu, Xiaomei; Xiang, Fenfen; Li, Xiaoxiao; Zhang, Mengzhe; Zheng, Jin; Kang, Xiangdong; Wu, Rong (Frontiers in Endocrinology, 2023)
Objective: Increased inflammation and cytokine levels are considered risk factors and promoters of preterm birth (PTB). However, the regulatory mechanism of pregnancyrelated inflammation remains unclear. Toll-like receptor 4 (TLR4) plays a critical role in inflammatory responses in various diseases. Therefore, our study aimed to investigate whether TLR4 is involved in the inflammatory responses during uterine activation for labor, with the goal of identifying potential biomarkers for uterine activation at term. We used flow cytometry to detect TLR4 expression on CD14+ maternal blood monocytes in the first, second, and third trimesters. ELISA was employed to measure TLR4 and cytokines levels in the maternal serum of term non-labor (TNL), term labor (TL) women and LPS induced preterm labor and PBS injected controls. TLR4siRNA was transfected into the human myometrial smooth muscle cells (HMSMCs), which were subsequently treated with IL-1β. The mRNA and protein levels of TLR4, uterine contraction-related protein connexin 43 (CX43), oxytocin receptor (OTR), MAPK/NF-κB signaling pathway, and cytokines were analyzed using qRT-PCR, western blotting, and immunohistochemistry.The study revealed TLR4 expression on CD14+ maternal blood monocytes was higher in the third trimester group compared to the first and second trimester groups (p<0.001). Maternal serum concentrations of TLR4 and cytokines were significantly higher in the TL group than the TNL group (p<0.001). TLR4, OTR, CX43, activated MAPK/NF-κB expression, and cytokines levels were upregulated in TL group, and similarly significantly higher in the LPSinduced preterm group than in the control group. Using the HMSMCs we demonstrated that TLR4siRNA transfection suppressed contractility. Interfering with TLR4 expression reduced the expression of OTR, CX43, cytokines, and MAPK/NF-κB activation. There was a significant positive relationship between TLR4 expression and the inflammatory status in the myometrium. ROC analysis indicated that TLR4 and cytokines may serve as potential biomarkers for predicting uterine activation for labor.Our data suggest that TLR4 and cytokines can act as stimulators of uterine activation for labor at term. Furthermore, the MAPK/NF-κB pathway appears to be one of the potential signaling pathways mediating TLR4's regulation of parturition initiation.